UPAYA PENINGKATAN AKTIVITAS BELAJAR IPS DENGAN METODE DEMONSTRASI PADA SISWA KELAS V SEKOLAH DASAR NEGERI 1 GEDUNG AIR BANDAR LAMPUNG TP 2019/2020 - Saring, Yahno (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
Based on the pre-research results of the implementation of social studies learning (1) learning activities are still dominated by teachers so that students are less active in learning (2) the method used in social studies learning is the lecture method, where the information/concepts being studied are notified or presented by the method. lecture only; (3) in the learning process the teacher does not provide reinforcement in the form of providing motivation to students. The problem formulation in this study is "Whether the use of demonstration methods can increase social studies learning activities in class V SD Negeri 1 Gedung Air Bandar Lampung for the 2019/2020 academic year. The purpose of this study was to improve social studies learning activities in class V SD Negeri 1 Gedung Air Bandar Lampung for the 2019/2020 academic year. The results of the research on the social studies learning process using the demonstration method in class V SD Negeri 1 Gedung Air Bandar Lampung for the 2019/2020 academic year, were as follows: In cycle 1 teacher performance reached 67% and student activity reached 63%. In the second cycle, the teacher's performance reached 78% and student activity reached 71%. In the third cycle the teacher's performance reached 88% and student activity reached 92%.